Case of acute paraspinal pyomyositis in an elderly diabetic secondary to spread from urinary tract infection. (23rd August 2018) - Unnikrishnan, Dileep; Delacruz, Maria Amanda; Saha, Anamika; Daniels, Richard
Abstract : A 73-year-old woman with medical history of diabetes and hypertension presented with right-sided back pain and night sweats of 1 month duration. On physical examination, there was costovertebral angle tenderness and her urinalysis was indicative for urinary tract infection. She was admitted and managed with intravenous antibiotics. On initial imaging, there was a right-sided retroperitoneal mass adjacent to right kidney. This was investigated further with MRI, which showed diffuse inflammation of right paraspinal muscles with two loculated abscesses. The abscesses were aspirated and the culture sent grew Streptococcus agalactiae (Group B Streptococcus) and the patient was treated with 6-week course of intravenous antibiotics.